Americans 1963 - Miller, Dorothy C. (New York : The Museum of Modern Art, 1963)
Anuszkiewicz, Richard ; Bontecou, Lee ; Chryssa ; Hazelet Drummond, Sally ; Higgins, Edward ; Indiana, Robert ; Kohn, Gabriel ; Lekakis, Michael ; Lindner, Richard ; Marisol ; Thure Oldenburg, Claes ; Reinhardt, Ad ; Rosenquist, James ; Seley, Jason ; Simpson, David
Americans 1963, The Museum of Modern Art, New York, 20.05 - 18.08.1963
boek
Keywords: Amerika